RESOURCE PROVISION IN THE ENTERPRISE’S ECONOMIC SECURITY SYSTEM: CHALLENGES OF THE MODERN GLOBAL SECURITY ENVIRONMENT AND ECONOMIC CONFLICTS - GARAFONOVA, Olga; YANKOVOY, Roman; DVORNYK, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The economic security of an enterprise is a crucial condition for its sustainable operation and growth. It involves not only protection from financial losses but also protection against potential threats such as economic crises, competition, fraud, as well as management and technical risks. To ensure economic security, it is necessary to develop a system of strategic resource management, which includes: аssessing potential threats and developing plans to minimize them; improving the efficiency of the use of financial, material, and human resources; developing and implementing internal standards and procedures to reduce possible financial and management risks; continuous monitoring and adjusting strategies according to changes in the market and the economy as a whole. The article analyzes resource support in the economic security management system of an enterprise. It is established that in modern conditions of economic instability and fierce competition, the economic security of an enterprise is a key condition for its Sustainable Development. Resource provision is a basic component of the economic security system, as it provides the enterprise with everything necessary for effective functioning, adaptation to external threats and implementation of strategic goals. Resource provision is the basis of an enterprise’s activity, which ensures its ability to function stably and efficiently even in conditions of economic instability or threats. It performs a number of important functions in the economic security management system. Resource allocation is used to ensure the sustainability, efficiency, and adaptability of an enterprise. It serves as the basis for Strategic Management of economic security and guarantees competitiveness in a dynamic economic environment. Improving resource provision at the enterprise requires a comprehensive approach, which includes optimization of resource management processes, introduction of modern technologies and strategic planning.